Part Objects and Their Location - Madsen, Ole Lehrmann; Møller-Pedersen, Birger (DAIMI Report Series, 1992)
The notion of location of part objects is introduced, yielding a reference to the containing object. Combined with locally defined objects and classes (block structure), singularly defined part objects, and references to part objects, it is a powerful language mechanism for defining objects with different aspects or roles. The use of part objects for inheritance of code is also explored.